Say it ain't Steno : a microbiology nudge comment leads to less treatment of Stenotrophomonas maltophilia respiratory colonization - Boettcher, Stormmy R; Kenney, Rachel M; Arena, Christen J; Beaulac, Amy E; Tibbetts, Robert J; Shallal, Anita B; Suleyman, Geehan; Veve, Michael P (Infection control and hospital epidemiology, 2025)
To describe the effect of a (SM) respiratory culture nudge on antibiotic use in colonized patients. IRB-approved quasi-experiment. Five acute-care hospitals in Michigan. Adult patients with SM respiratory culture between 01/01/2022 and 01/27/2023 (pre-nudge) and 03/27/2023-12/31/2023 (post-nudge). Patients with active community/hospital/ventilator-acquired pneumonia or who received SM-targeted antibiotics at the time of culture were excluded. A nudge comment was implemented 02/2023 stating: " is a frequent colonizer of the respiratory tract. Clinical correlation for infection is required. Colonizers do not require antibiotic treatment." The primary outcome was no treatment with SM-therapy; secondary outcomes were treatment with SM-therapy ≥72 hrs, length of stay, and in-hospital, all-cause mortality. Safety outcomes included antibiotic-associated adverse drug events (ADEs). 94 patients were included: 53 (56.4%) pre- and 41 (43.6%) post-nudge. Most patients were men (53, 56.4%), had underlying lung disease (61, 64.8%), and required invasive ventilatory support (70, 74.5%). Eleven (11.7%) patients resided in a long-term care facility. No treatment with SM therapy was observed in 13 (23.1%) pre- versus 32 (78.0%) post-nudge patients ( <0.001). There were no differences in secondary outcomes. Antibiotic-associated ADEs were common (33/41, 76%) in patients who received ≥72hrs of SM-therapy: fluid overload (18, 44%), hyponatremia (17, 42%), elevated SCr (12, 29%), hyperkalemia (5, 12%). After adjustment for confounders, post-nudge was associated with 11-fold increased odds of no treatment with SM-therapy (adjOR, 11.72; 95%CI, 4.18-32.83). A targeted SM nudge was associated with a significant reduction in treatment of colonization, with similar patient outcomes. SM-treated patients frequently developed antibiotic-associated ADEs.